Large-FSR Thermally Tunable Double-Ring Filters for WDM Applications in Silicon Photonics - C. L. Manganelli; P. Pintus; F. Gambini; D. Fowler; M. Fournier; S. Faralli; C. Kopp; C. J. Oton (IEEE Photonics Journal, 2017)
We present the design procedure and experimental results of thermally tunable double ring resonators for integrated wavelength division multiplexing applications. A detailed analytical model specific for double rings is described, and a modified racetrack geometry using Bezier bends is used to reduce bending loss. We demonstrate devices with a free-spectral-range up to 2.4 THz (19 nm) around 1550 nm and nonadjacent channel rejection higher than 35 dB. The experimental results of thermally tunable double ring resonators is also presented with doped silicon integrated heaters, allowing the device to be used as a tunable filter or a switch.